The obstacles affecting the tax reform in Iraq: Applied research in the General Authority for Taxation (Journal of Accounting and Financial Studies ( JAFS ), 2018)
In light of this, attention should be paid to tax reform as part of a comprehensive economic reform program. Therefore, the research started from the problem of the weak efficiency of the tax reform process in the General Authority for Taxation, as well as the need to know the addition of new taxes or increase taxes.The research aims study the relative importance of each disabled person, whether organizational, human, financial, legislative or technical. The research led to a number of conclusions, the most important of which were that the financial obstacles occupy the highest importance of the other obstacles and for the success of the tax reform, the material resources must be provided in order to provide the necessary reforms. The most important recommendations reached by the research are to divide the tax reform programs into stages the state budget.Keyword: Reform, Constraints, Tax